PELAKSANAAN URUSAN PEMERINTAHAN PEKERJAAN UMUM BIDANG BINA MARGA TERHADAP INFRASTRUKTUR JALAN DI KABUPATEN KUANTAN SINGINGI TAHUN 2015 - Hesti Larasani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the cause of the success of the construction of roads in the district of Pangean (Teluk Pauh) by 2015 and to determine the factors - factors that limit the success of the road infrastructure in the district of Pangean (Teluk Pauh) in 2015. The study used qualitative research methods to study descriptive, which can be interpreted as a problem-solving process that describes the situation investigated by the research subjects were based on the facts that appear during the study and then based on the theories that exist. Implementation of Administration of Public Works of Highways on Road Infrastructure Regency Kuantan in 2015 showed that there is good communication between government and society in the development of road infrastructure in the village of Teluk Pauh district Pangean Regency Kuantan, it can be seen from the process of planning, implementation, monitoring , up to its utilization by the community. In addition, public awareness of the importance of road infrastructure is also a major contribution to improving infrastructure and the quality of the road in the village of Teluk Pauh district Pangean Regency Kuantan.Keywords: Public Administration of Highways, Roads Infrastructure